(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article emphasizes that the implementation of defense procurement under martial law serves as the basis for maintaining the state’s defense capability, providing security and defense forces with the latest types of weapons and equipment, without which it is currently impossible to successfully conduct combat operations, plan and implement any tactical plan on the battlefield. It is noted that the rethinking of the sphere of public procurement in Ukraine took place in the light of the events of the Revolution of Dignity, the emergence of electronic platforms that allow the general public to effectively influence the honesty and integrity of public administration decisions in the field of public procurement. It is determined that the regulatory influence of the state in the course of organizing defense procurement under martial law should be inseparable from taking into account certain features, which in their aggregate determine the vector of the relevant state policy, become the basis for the development of domestic legislation and the practice of its implementation. Such features include the presence of a coordinated defense planning mechanism, which, under martial law, allows for the definition of a clear vector for planning defense procurement in the context of taking into account a wide range of factors, patterns, and potential opportunities not only in the defense sector, but also in the economic, foreign policy, and other spheres; a comprehensive analysis of risks, in particular corruption risks, in order to minimize which, special attention should be paid to the formation of high moral and ethical values among military personnel and defense sector employees.